HUBUNGAN LAMANYA HEMODIALISA DENGAN TERJADINYA ANEMIA PADA PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT MURNI TEGUH SUDIRMAN JAKARTA - Taufik, Windri; Simatupang, Lenny Lusia (Excellent Midwifery Journal, 2024)
A patient with chronic kidney failure is someone who experiences permanent kidney damage where the patient requires renal replacement therapy, so that they are able to survive independently. The main goal of hemodialysis therapy is to restore the balance of intracellular and extracellular fluids that are disturbed due to damaged kidney function. Anemia experienced by dialysis patients is a common complication whose prevalence increases from 8% grade 1 to 53% grade 5 who do not receive dialysis (Michalopoulos al, 2022). The results of a preliminary study conducted in the Hemodialysis Room of Murni Teguh Sudirman Hospital, Jakarta, obtained 28 CKD patients undergoing routine hemodialysis from January to June 2024. The purpose of this study was to determine the relationship between the duration of hemodialysis and the incidence of anemia in chronic kidney failure patients at Murni Teguh Sudirman Hospital, Jakarta. The research design used in this study was an analytical observational study with a cross-sectional approach. analytical observational research. The sample in the study was 28 respondents using total sampling, statistical tests using Spearman rank, the study took place on July 10-August 10, 2024. The results of the study There is a Relationship Between the Duration of Hemodialysis and the Occurrence of Anemia in Chronic Kidney Failure Patients at Murni Teguh Sudirman Hospital, Jakarta with the results of the Spearman rank test data analysis obtained p value = 0.043 which means it is smaller than α = 0.05 with a correlation confficient level of 0.826 and a positive relationship direction.